Community Development Centre (CDC): A Covenant with the Baiga (Tribe) - Shantanu Menon; Satender Rana; Kushagra Merchant; Aruna Pandey (My University, 2022)
This case study documents the journey of CDC and shows how the organization has created a resilient and responsive organizational culture in a remote and resource starved environment to address multiple developmental challenges of the region, particularly the Baiga tribe.
Case Study
Keywords: Indigenous Baiga Tribe; Forest Communities; Tribal Development